Birth preparedness and complication readiness assessment among antenatal and postnatal mothers at government hospital, in urban Bengaluru - Sangeetha M.D; Jagadish Ganagi; Darshan H.S; Neha Annet Joy; Akarsh KR (Al Ameen Journal of Medical Sciences)
Background: Maternal mortality remains a significant public health challenge, particularly in developing countries like India. Birth Preparedness and Complication Readiness (BPACR) is a critical component of antenatal care recommended by the World Health Organization (WHO) to reduce maternal mortality. The maternal mortality ratio (MMR) of Karnataka is 92 per 100,000 live births in SRS 2016-18. Since Karnataka had the highest MMR ratio among the southern states of India the present study was thus conducted to determine the BPACR among antenatal and postnatal women and assess the factors related to it. Methods: A community-based cross-sectional study was conducted at a government hospital in Bengaluru. A sample of 105 antenatal mothers in their third trimester and postnatal women (age ≥ 18 years) attending the hospital was included. Data were collected using a pretested questionnaire that assessed various indicators related to BPACR, including knowledge of danger signs, health service utilization, and preparation for childbirth. Results: The study found a high BPACR index of 78%, with 17% of women exhibiting good BPACR. Knowledge of danger signs during pregnancy was high (95.2%), but lower for labor (51.4%) and postpartum (44.7%) periods. Fewer women knew about danger signs in neonates (46.6%). Regarding preparedness, 97.1% of women had identified transport arrangements, while only 25.7% knew about the need for blood transfusion during delivery. Awareness regarding the Karnataka Mathrushree Scheme was low at 25.7%. Conclusion: The study highlights a relatively high level of BPACR among antenatal and postnatal mothers in urban Bengaluru. Strengthening education and counseling during antenatal care, involving family members, and community awareness campaigns can improve BPACR and ultimately contribute to safer motherhood.